Construction and design of prestressed concrete segmental bridges - Podolny, Water (John Wiley & Sons, 1982)
An extensively illustrated handbook summarizing the current state of the art of design and construction methods for all types of segmental bridges. Covers construction methodology, design techniques, economics, and erection of girder type bridges; arch, rigid frame, and truss bridges; cable-stayed bridges; and railroad bridges.